Manajemen Pembinaan Akhlak Mulia pada Siswa Melalui Program Ekstrakurikuler Keagamaan di SD Islam Terpadu Se-Kecamatan Panyabungan Kabupaten Mandailing Natal - Nurhayani, Nurhayani; Zulhimma, Zulhimma; Hasibuan, Zainal Efendi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this research is to describe the management of noble character development through religious extracurricular activities in Integrated Islamic Elementary Schools in Panyabungan District, Mandailing Natal Regency. The study employed a descriptive qualitative method using observation, interviews, and documentation as data collection techniques. The subjects included principals, vice principals for student affairs, and extracurricular supervisors at SD IT Al-Munawwar, SD IT Al-Husnayain, and SD IT Al-Furqon. Data were analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that management functions—planning, organizing, implementing, and supervising—were systematically applied. Planning was carried out through annual programs, syllabi, and lesson plans; organizing involved a clear division of responsibilities; implementation was conducted regularly using methods of exemplification, habituation, and wise advice; while supervision was done through periodic evaluations. Supporting factors included adequate facilities, a religious school culture, and teacher involvement, whereas inhibiting factors were the lack of focus among some students. Thus, religious extracurricular activities significantly contribute to the development of students’ noble character in Integrated Islamic Elementary Schools